2003
DOI: 10.1016/j.virusres.2003.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of N protein self-association in coronavirus ribonucleoprotein complexes

Abstract: Mouse hepatitis virus (MHV) nucleocapsid (N) protein binds to the large, single-stranded, positive-sense viral genomic RNA to form a helical nucleocapsid structure in mature virions. In addition N protein binds the intracellular form of the genomic RNA, all of the MHV subgenomic mRNAs, and expressed non-MHV RNA transcripts to form ribonucleoprotein (RNP) complexes in infected cells. Among the intracellular viral RNP complexes, only the genomic RNP complex is packaged into virus particles. The present study dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 50 publications
3
59
0
Order By: Relevance
“…As such, both proteins are capable of multimerization and RNA binding (Narayanan et al, 2003;Luo et al, 2005;Zú ñiga et al, 2007). In addition, both proteins have gene regulatory activity and can repress IFN production (Kopecky-Bromberg et al, 2007;Ye et al, 2007).…”
Section: Sars-cov N Protein Does Not Modulate Fgl2 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, both proteins are capable of multimerization and RNA binding (Narayanan et al, 2003;Luo et al, 2005;Zú ñiga et al, 2007). In addition, both proteins have gene regulatory activity and can repress IFN production (Kopecky-Bromberg et al, 2007;Ye et al, 2007).…”
Section: Sars-cov N Protein Does Not Modulate Fgl2 Expressionmentioning
confidence: 99%
“…The coronavirus nucleocapsid (N) protein is a relatively conserved structural protein that binds genomic RNA and plays an important role in viral RNA synthesis, viral assembly and formation of the RNA replication complex (Narayanan et al, 2003;Almazán et al, 2004). Intracellularly, coronavirus N protein localizes to the cytoplasm, in which it interacts with M protein to form an icosahedral core (Hurst et al, 2005).…”
mentioning
confidence: 99%
“…[3][4][5] The N protein is a multifunctional phosphoprotein that encapsidates the viral genome and plays a role in virus assembly. 6,7 N also appears to be involved in viral RNA replication and/or transcription. 8,9 The aim in this study was to provide a comprehensive view of the subcellular localization of the main SARS-CoV structural proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Since the end of the SARS outbreak, there have been 17 identified SARS-associated coronavirus (SARS-CoV) infections, 6 from direct laboratory exposure, 1 of which resulted in community transmission to seven individuals, and 4 sporadic, community-acquired infections (9). Since additional cases may occur and could, if undetected, quickly lead to another global outbreak, it is important to continue to improve our ability to reliably monitor SARS-CoV infections (3,16,18).As with other coronaviruses, the spike (S) and nucleocapsid (N) proteins are abundantly expressed during virus infection and are most effective among the coronavirus structural proteins at inducing antibody responses (10,14,15,23). Previous studies have demonstrated the utility of anti-N and anti-S proteins in the diagnosis of SARS-CoV infections (2,5,12,21).…”
mentioning
confidence: 99%
“…As with other coronaviruses, the spike (S) and nucleocapsid (N) proteins are abundantly expressed during virus infection and are most effective among the coronavirus structural proteins at inducing antibody responses (10,14,15,23). Previous studies have demonstrated the utility of anti-N and anti-S proteins in the diagnosis of SARS-CoV infections (2,5,12,21).…”
mentioning
confidence: 99%